Potential therapeutic effects of IL28RA inhibition on acute myocardial infarction through phosphorylated JAK1/STAT1 signaling pathways - Ge Gong; Xiangxuan Chen; Xinghu Zhang; Jian Yin; Wenhui Wan (Scientific Reports)
Abstract While current coronary intervention therapies and surgical bypass procedures are widely utilized, the treatment of acute myocardial infarction (AMI) in the elderly continues to pose significant challenges. Following AMI, the body’s immune system is activated, resulting in the release of inflammatory mediators that exacerbate myocardial damage. Interleukin 28A (IL28A) and interleukin 28B (IL28B) may play a role in immune regulation post-AMI by specifically binding to interleukin 28 receptor alpha (IL28RA). However, the precise underlying mechanisms remain incompletely understood. This study aims to investigate the levels of IL28A and IL28B following AMI, as well as the protective effects of inhibiting IL28RA expression in the context of AMI and its potential mechanisms. We analyzed serum samples from 55 patients with AMI and 41 control individuals using ELISA to evaluate the levels of IL28A and IL28B, as well as to assess their correlation with the clinical parameters of the patients. Additionally, we established a mouse model of AMI and employed intramyocardial injection of lentivirus to knock down IL28RA in the myocardium. Echocardiography was utilized to compare structural and functional changes, while HE staining was conducted to analyze the infarct area and assess changes in myocardial tissue and cell morphology. The expressions of IL28A, IL28B, IL28RA, and JAK1/STAT1 pathway-related proteins in the infarct area were compared through immunofluorescence and Western blot analysis. Finally, TUNEL staining and the BAX/Bcl2 ratio were utilized to evaluate cardiomyocyte apoptosis. The study demonstrated that serum IL28A levels in patients with AMI were significantly elevated compared to those in normal controls, whereas IL28B levels were significantly reduced. Additionally, both IL28A and IL28B levels exhibit a linear relationship with high-density lipoprotein (HDL) and body mass index (BMI). In a mouse model, cardiac function deteriorated and ventricular structural changes were observed 14 days post-myocardial infarction relative to controls. The expressions of IL28A and IL28RA were significantly upregulated in the myocardium of the infarcted area, while IL28B levels showed no significant variation. Additionally, the ratios of p-JAK1/JAK1 and p-STAT1/STAT1 were significantly increased, accompanied by a notable rise in apoptotic cells within the myocardial infarction area. Importantly, the knockdown of IL28RA expression in the infarcted region effectively mitigated these alterations. These results suggest that IL28A but not IL28B contributes to the process post-AMI and may induce cardiomyocyte apoptosis through the JAK1/STAT1 pathway in conjunction with IL28RA.